1997
DOI: 10.2307/3343311
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Unemployment on Health: A Review of the Evidence

Abstract: Objective: To review the scientific evidence supporting an association between unemployment and adverse health outcomes and to assess the evidence on the basis of the epidemiologic criteria for causation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
288
1
15

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(311 citation statements)
references
References 43 publications
(13 reference statements)
7
288
1
15
Order By: Relevance
“…The results of this research are generally supportive of those of a number of population-level studies [Brenner, 1983;Ahmed et al, 1989;Franks et al, 1991;Brackbill et al, 1995;Jin et al, 1995;Weber and Lehnert, 1997] which reported cross-sectional associations between employment rates and cardiovascular or cerebrovascular mortality. It is more difficult to relate our findings to those reported in individual-level longitudinal studies [Kasl and Cobb, 1980;Iversen et al, 1989;Janlert, 1992;Schnall et al, 1992], which are far fewer, and whose results are somewhat equivocal.…”
Section: Discussionsupporting
confidence: 86%
“…The results of this research are generally supportive of those of a number of population-level studies [Brenner, 1983;Ahmed et al, 1989;Franks et al, 1991;Brackbill et al, 1995;Jin et al, 1995;Weber and Lehnert, 1997] which reported cross-sectional associations between employment rates and cardiovascular or cerebrovascular mortality. It is more difficult to relate our findings to those reported in individual-level longitudinal studies [Kasl and Cobb, 1980;Iversen et al, 1989;Janlert, 1992;Schnall et al, 1992], which are far fewer, and whose results are somewhat equivocal.…”
Section: Discussionsupporting
confidence: 86%
“…Sullivan and von Wachter (2006, using administrative data from two US states, estimate a 15-20% excess risk of death in the 20 years following a job loss. Eliason and Storrie (2009) provide similar evidence 8 Cook (1985), Morris and Cook (1991) and Jin et al (1995) survey the early literature. Platt (1984) documents the effects of unemployment on suicidal behavior.…”
Section: Related Literaturementioning
confidence: 69%
“…Official rates underestimate the true extent of unemployment as they do not include persons who have stopped looking for work and have left the labor force or those who desire full-time work but are only working part-time (20). This later group can be referred to as being "underemployed" (20).…”
mentioning
confidence: 99%
“…Official rates underestimate the true extent of unemployment as they do not include persons who have stopped looking for work and have left the labor force or those who desire full-time work but are only working part-time (20). This later group can be referred to as being "underemployed" (20). The adverse effects of lack of full-time work may differ in groups of unemployed persons, those who have left the labor force due to an inability to find work or are only working parttime.…”
mentioning
confidence: 99%